Combination of subxiphoid and intercostal uniportal video-assisted thoracoscopic surgery for bilateral lung lesions: report of two cases and review of the literature. Issue 5 (4th July 2017) - Wang, Linlin; Ge, Lihui; Yang, Xueying
ABSTRACT: Uniportal video-assisted thoracic surgery (VATS) is carried out to reduce postoperative pain after treatment of thoracic diseases. Here, we report a novel method that combines a subxiphoid and intercostal uniportal VATS approach that can be used to treat bilateral pulmonary lesions simultaneously. The first case is a 50-year-old female with bilateral pulmonary lesions who received left lower lobectomy associated with right middle lobe wedge resection synchronously; the other case is a 14-year-old male who was admitted for resection of bilateral lung metastases as a result of previous osteosarcoma. We combined a subxiphoid approach with intercostal uniportal surgical procedure for bilateral pulmonary lesions. Less postoperative pain, faster postoperative recovery, and a better aesthetic effect are possible superiorities of this method if patients are selected carefully. Our results show that the combining of a subxiphoid approach with intercostal uniportal VATS is a feasible and efficient surgical procedure for bilateral pulmonary lesions, with good outcomes. Moreover, this procedure is more suitable for patients with bilateral pulmonary lesions.